The impact of team orientation on teamwork engagement : having intragroup conflict as moderator - Gommel, Ana Isa Dupret Hopffer Almada (2017)
Teams in organizational settings have a pivotal and vital role in generating the success of a company and the development of each employee. Therefore, the central question is: how can teams engage in order to achieve their maximum performance? Because of the scarcity of empirical studies, the present study aims to analyze the influence that team orientation – an individual characteristic that takes behaviors of others into account, as well as preferences to work in a group rather than alone - might have on the emergence of teamwork engagement, and consequently on team effectiveness. In addition the moderator effect of intragroup conflicts on the relationship between team orientation and teamwork engagement was also tested. The sample is composed of 99 employees belonging to 22 Hostels in Lisbon. The questionaries and the data collection was implemented in a structured way, that all of the employees, in every category (cleaning staff, receptionist, and managers), could answer. The results showed that, contrary to what we expected, the intragroup conflicts do not moderate the relation of individual characteristic - Team orientation- and teamwork engagement. However, the positive relationship was found between the teamwork engagement and effectiveness of teams but not between the orientation to work in a team and the TWE. It is believed that due to the small sample size, the assumptions made could not support the proposed model. In addition to complete, it was conferred the theoretical implications and practical research and finally presented a set of suggestions for future studies.